Evidence of Substorm‐Driven Penetration Electric Field Contributions to Low‐Latitude Phenomena: Enhanced Upward Drifts, Plasma Bubble Development and Severe Scintillation - J. Sousasantos; F. S. Rodrigues; B. G. Fejer; R. W. Eastes; A. O. Moraes (Space Weather)
Abstract In this work, it is demonstrated that substorm‐driven penetration electric fields can efficiently enhance the upward plasma transport, favoring the development and structuring of plasma irregularities and the occurrence of scintillation on L‐band signals. While most previous studies focus on investigating penetration electric fields during intense geomagnetic storms, here, the period used (April 01–05, 2020) was under very mild geomagnetic activity (−27 nT ≤ SYM‐H ≤ 6 nT), so that interplanetary and disturbance dynamo contributions are minimized. This period comprised the same seasonal and solar flux conditions, while undergoing multiple short‐lived substorms, making it well‐suited to evaluate unequivocally: (a) to what extent substorm‐driven penetration electric fields alter electrodynamical processes over low latitudes, and (b) how effective they are in contributing to the structuring of the early nighttime ionosphere and the subsequent occurrence of severe scintillation on L‐band signals. Ground‐based and space‐based multi‐instrument data sets were used. The results show that, even under weak geomagnetic activity, substorm‐driven penetration electric fields—despite being subtle and short‐lived—play a decisive role, enhancing the upward drifts, favoring the development of equatorial plasma bubbles and severe scintillation. The findings indicate that substorms with onsets coinciding with early nighttime are more impactful. This decisive contribution is more likely to be identified during late spring and early fall in the northern hemisphere (or vice versa in the southern hemisphere), when the prereversal vertical drifts are moderate—neither too small nor too large—and may have direct impacts on the day‐to‐day variability of equatorial plasma bubbles.